Retinoic acid has light-adaptive effects on horizontal cells in the retina - Weiler, Reto (The National Academy of Sciences, 1998)
Ambient light conditions affect the morphology of synaptic elements within the cone pedicle and modulate the spatial properties of the horizontal cell receptive field. We describe here that the effects of retinoic acid on these properties are similar to those of light adaptation. Intraorbital injection of retinoic acid into eyes of dark-adapted carp that subsequently were kept in complete darkness results in the formation of numerous spinules at the terminal dendrites of horizontal cells, a typical feature of light-adapted retinae. The formation of these spinules during light adaptation is impaired in the presence of citral, a competitive inhibitor of the dehydrogenase responsible for the generation of retinoic acid in vivo. Intracellularly recorded responses of horizontal cells from dark-adapted eyecup preparations superfused with retinoic acid reveal typical light-adapted spatial properties. Retinoic acid thus appears to act as a light-signaling modulator. Its activity appears not to be at the transcriptional level because its action was not blocked by actinomycin.